2003
DOI: 10.1292/jvms.65.679
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Lactoferrin but Not Transferrin Reflects Gonadal Function in Dogs

Abstract: ABSTRACT. Lactoferrin purified from canine seminal plasma by a three-step chromatography procedure had a molecular mass of 75.2 kDa and cross-reacted with antiserum to equine seminal plasma lactoferrin. Seminal plasma lactoferrin concentrations were determined by a competitive enzyme-linked immunosorbent assay (ELISA) by using rabbit anti-equine lactoferrin antibody and alkaline phosphataselabeled goat anti-rabbit IgG antibody in 14 normal dogs and found to range from 12 to 197 µg/ml, with a mean value of 77 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In adults, higher levels of lactoferrin are present in milk and colostrum (Masson and Heremans, 1971;Brock, 1980). It is also found in most mucosal secretions such as uterine fluid, vaginal secretion, seminal fluid, saliva, bile, pancreatic juice, small intestine secretions, nasal secretion, and tears (Masson et al, 1966;Baker, 1994;Levay and Viljoen, 1995;Lonnerdal and Iyer, 1995;Kikuchi et al, 2003;Baker and Baker, 2005).…”
Section: Sources Of Lactoferrin In the Organismmentioning
confidence: 99%
“…In adults, higher levels of lactoferrin are present in milk and colostrum (Masson and Heremans, 1971;Brock, 1980). It is also found in most mucosal secretions such as uterine fluid, vaginal secretion, seminal fluid, saliva, bile, pancreatic juice, small intestine secretions, nasal secretion, and tears (Masson et al, 1966;Baker, 1994;Levay and Viljoen, 1995;Lonnerdal and Iyer, 1995;Kikuchi et al, 2003;Baker and Baker, 2005).…”
Section: Sources Of Lactoferrin In the Organismmentioning
confidence: 99%
“…From these findings, it may be considered that Lf is involved in sperm maturation in the epididymis. Recently, we found the positive correlation between the seminal plasma Lf concentration and the sperm density in dogs [10], suggesting that Lf secretion relates to gonadal function. The present study was performed to determine whether there is also this relationship in mammals other than dogs.…”
mentioning
confidence: 88%
“…Recently, we found that the seminal plasma Lf concentration positively correlates with the sperm concentration in dogs [10], although the secretion site of Lf in the canine reproductive system remains to be clarified. This study revealed that there is also the same relationship in horses, suggesting that Lf secretion in equine epididymis is closely related to gonadal function.…”
mentioning
confidence: 98%
See 2 more Smart Citations